Colored self-leveling red-mud-based fully-regenerated high-strength mortar and preparation method thereof

Through the preparation method of color self-leveling red mud-based fully recycled high-strength mortar, the resource utilization problem of fine aggregates, red mud and waste pigments of construction waste concrete are solved, and efficient and low-carbon resource utilization and environmental protection are achieved.

CN119613023APending Publication Date: 2025-03-14GUANGXI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411762277.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art fails to effectively utilize fine aggregates, red mud and waste pigments of construction waste concrete, resulting in waste of resources and environmental pollution.

Method used

The preparation method of color self-leveling red mud-based fully regenerated high-strength mortar is adopted. By mixing and processing components such as dry powder activated red mud, building regenerated fine powder, building regenerated sand and waste pigment, regenerated mortar with high strength and low carbon characteristics is prepared.

Benefits of technology

It has achieved efficient utilization of red mud, construction solid waste materials and waste pigments, reduced the demand for natural sand and gravel, reduced environmental pollution, and the production process is low-carbon, with high strength and good self-leveling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613023A_ABST
    Figure CN119613023A_ABST
Patent Text Reader

Abstract

The invention relates to the field of solid waste resource utilization research, in particular to colored self-leveling red-mud-based fully-recycled high-strength mortar and a preparation method thereof, and the colored self-leveling red-mud-based fully-recycled high-strength mortar comprises the following components in parts by mass: 60-100 parts of solid waste cementing material, 30-50 parts of mortar recycled aggregate, 5-10 parts of recycled pigment and 2-10 parts of self-leveling agent. By adopting the colored self-leveling red-mud-based fully-regenerated high-strength mortar material disclosed by the invention, a large amount of industrial solid wastes such as red mud, construction wastes and waste pigments can be recycled, the material is convenient and efficient to construct, high in strength and good in flowability, the dependence on natural raw materials can be reduced, the cyclic utilization of solid waste resources is promoted, and the cost is reduced. Therefore, carbon emission is reduced, environmental pollution is reduced, more material choices are provided for the building industry, and different engineering requirements are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the research field of solid waste resource utilization, and specifically is a colored self-leveling red mud-based fully recycled high-strength mortar and a preparation method thereof. Background Art

[0002] Urbanization and industrialization are major processes in the world today. In the process of promoting urbanization and industrialization, a large amount of abandoned construction solid waste materials and industrial solid waste materials are generated. In some large cities, the annual amount of construction waste can reach tens of millions of tons or even hundreds of millions of tons. In addition, red mud is one of the typical industrial solid waste materials. According to statistics, my country's annual output of alumina is about 75 million tons. Every 1t of alumina produced emits about 0.8 to 2.5t of red mud, and the annual red mud produced is as high as nearly 100 million tons. The discharge of red mud occupies a large amount of land resources and causes huge pollution and harm to the ecological environment, which has seriously affected the sustainable development of the alumina industry. After a large amount of red mud is produced, if it cannot be effectively utilized, it can only be landfilled. Therefore, it is extremely important to efficiently utilize and dispose of construction solid waste and industrial solid waste.

[0003] At present, for construction waste concrete, domestic and foreign researchers mostly crush it to obtain coarse aggregate, strengthen it through physical and chemical modification methods, and then replace part of the natural aggregate and add it to concrete. However, fine aggregate is generally landfilled and has not been effectively applied; for red mud industrial solid waste materials, it is currently mainly stored, occupying a large amount of land resources, and the discharge of high-alkali wastewater will pollute the surrounding soil and water sources. Although current scholars have proposed many red mud de-alkali schemes, such as water washing de-alkali method, acid neutralization method, wet carbonization de-alkali method, etc., there is still a large amount of red mud that has not been effectively utilized. Furthermore, some scholars have proposed using red mud as a solid waste recycling material to prepare red mud-cement composite mortar, but the recycled mortar is still mainly cement, using non-renewable resources natural sand, and with the increase of red mud content, the fluidity and strength of the red mud-cement composite mortar are both on a downward trend. The contradiction between fluidity and strength has not been well resolved, and it is difficult to achieve the goal of large-scale disposal of red mud.

[0004] The resource utilization of construction waste concrete and red mud is a significant problem. The existing technology has not yet solved the problem of the utilization of construction waste concrete fine aggregate, the large-scale low-carbon utilization of red mud, and the reuse of waste pigments. Therefore, it is urgent to find a method for the coordinated utilization of regenerated construction solid waste, red mud and waste pigments. Summary of the invention

[0005] Based on the problems existing in the prior art, the present invention proposes a colored self-leveling red mud-based fully regenerated high-strength mortar and a preparation method thereof, which can realize the comprehensive utilization of red mud and regenerated micropowder, regenerated sand and waste pigments, achieve the purpose of efficient utilization of solid waste resources, and effectively replace cement cementitious materials. It has the characteristics of low-carbon production and high-strength performance, and is adapted to the current trend of technological development.

[0006] The technical solution adopted by the present invention is:

[0007] A colored self-leveling red mud-based fully recycled high-strength mortar material, comprising the following components in parts by weight:

[0008] Solid waste cementitious materials: 60-100 parts.

[0009] Mortar recycled aggregate: 30-50 parts.

[0010] Recycled pigment: 5-10 parts.

[0011] Self-leveling agent: 2-10 parts.

[0012] Furthermore, the solid waste cementitious material includes dry powder activated red mud and building recycled micro powder.

[0013] Furthermore, the mass fractions of the dry powder activated red mud and the building recycled micro powder are as follows:

[0014] Dry powder activated red mud: 40-60 parts;

[0015] Building recycled micro powder: 20-40 parts.

[0016] Furthermore, in the solid waste gelling material, the fineness of the dry powder activated red mud satisfies that the pass rate of 200 mesh is greater than 90%, the NaOH content is 3.5wt%-4.6wt%, and the water content is less than 0.3wt%.

[0017] Furthermore, the mass fraction of CaO in the building recycled micro-powder is greater than 20%; the fineness of the building recycled micro-powder satisfies the 0.075mm pass rate greater than 90%.

[0018] Furthermore, the mortar recycled aggregate is construction recycled sand that passes through two sieve holes of 0.15mm-0.075mm and 0.3mm-0.15mm. The construction recycled sand meets the requirements of a water content of less than 0.5wt%, a mud content of no more than 2wt%, and a plasticity index of no more than 7. The particle size pass rate of the construction recycled sand is as follows:

[0019] 0.3mm-0.15mm: 75%-84%;

[0020] 0.15mm-0.075mm: 19%-31%

[0021] Furthermore, the regenerated pigment is waste paint from oil painting or waste paint from printer, and its particle size does not exceed 1 micron. Common pigments are divided into dark tones of black, gray, and blue and bright tones of red, yellow, and green according to the brightness of the color.

[0022] Furthermore, the self-leveling agent includes a high-fluidity water-reducing agent and an anti-seepage agent, the high-fluidity water-reducing agent is aminosulfonate, and the anti-seepage agent is at least one of polyacrylamide and polyvinyl alcohol.

[0023] In addition, the present invention also provides a method for preparing a colored self-leveling red mud-based fully regenerated high-strength mortar, comprising the following steps:

[0024] S1. First, the red mud is dried in a dryer until its water content is less than 0.3wt%, and the dried red mud is ground and sieved to prepare a red mud dry powder with a fineness of more than 90% passing rate of 200 mesh, and then the red mud is activated at 800°C using a high-temperature heating device muffle furnace, and the NaOH content of the activated dry powder activated red mud must reach 3.5wt%-4.6wt%;

[0025] S2. Dry and sieve the construction recycled micro powder and construction recycled sand respectively, requiring the fineness of the construction recycled micro powder to meet the requirement that the passing rate of 0.075mm is greater than 90%, and the CaO mass fraction detection value is greater than 20%; the particle size passing rates of 0.15mm-0.075mm and 0.3mm-0.15mm of the construction recycled sand are required to reach 19%-31% and 75%-84% respectively, and the detection indicators meet the requirements that the water content is less than 0.5wt%, the mud content does not exceed 2wt%, and the plasticity index does not exceed 7;

[0026] S3. The dry activated red mud is mixed with the building recycled powder, and the mixture is evenly dry mixed in a mortar mixer for 90-120s to form a solid waste cementitious material, and then the solid waste cementitious material is mixed with the recycled aggregate in the mortar, and evenly dry mixed in a mortar mixer for 180-240s to form a recycled mortar;

[0027] S4. Add the recycled pigment component and mix evenly. The color of the mortar is the color of the design. Then add the self-leveling agent and mix evenly. The mortar is automatically weighed by the packaging machine and waterproofed and packaged for preservation.

[0028] The colored self-leveling red mud-based fully recycled high-strength mortar has an initial fluidity of 180±5 mm, a 30-minute fluidity of greater than 180 mm, an absolute dry compressive strength of more than 30 MPa, and an absolute dry flexural strength of more than 7 MPa.

[0029] The beneficial effects of the present invention include:

[0030] 1. The colored self-leveling red mud-based fully recycled high-strength mortar of the present invention can absorb a large amount of red mud, construction solid waste materials and waste pigments, reduce the demand for traditional building materials such as natural sand and stone, help protect natural resources, and reduce the impact of environmental pollution.

[0031] 2. The colored self-leveling red mud-based fully recycled high-strength mortar of the present invention has high strength, good self-leveling properties, strong integrity, an initial fluidity of 180±5mm, an absolute dry compressive strength of more than 30Mpa, and an absolute dry flexural strength of more than 7Mpa, and can effectively replace ordinary cement mortar.

[0032] 3. The preparation process of the present invention is simple, the application range is wide, and the construction efficiency can be improved.

[0033] Instruction Manual

[0034] Figure 1 The present invention is a preparation flow chart of a colored self-leveling red mud-based fully recycled high-strength mortar;

[0035] Figure 2 This is the dry mortar diagram of Example 1;

[0036] Figure 3 Embodiment 1 Mortar self-leveling effect diagram;

[0037] Figure 4 Strength comparison chart of Examples 1 to 4. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not limit the present invention.

[0039] Example 1

[0040] A colored self-leveling red mud-based fully recycled high-strength mortar comprises the following components in parts by mass: 60 parts of solid waste cementitious materials, including 40 parts of dry powder activated red mud and 20 parts of building recycled micropowder; mortar recycled aggregate: 30 parts of building recycled sand; 5 parts of recycled pigment; 2 parts of self-leveling agent: including 1 part of high-fluidity water reducing agent and 1 part of anti-seepage agent.

[0041] Among them, the pass rate of dry powder activated red mud with a fineness of 200 mesh is 92%, the NaOH content is 3.5wt%, and the water content is 0.12wt%; the CaO mass fraction of building recycled micropowder is 24.1%, and the pass rate of 0.075mm fineness is 93%; the pass rate of building recycled sand 0.15mm-0.075mm is 19%, the pass rate of 0.3mm-0.15mm is 75%, the water content is 0.15wt%, the mud content is 1.3wt%, and the plasticity index is 5; the recycled pigment is a waste pigment from a printer, the main colors are black, gray and blue, and the particle size is 0.5 microns; in the self-leveling agent, the high-fluidity water reducer is aminosulfonate, and the anti-seepage agent is polyacrylamide.

[0042] The preparation process is as follows:

[0043] S1. First, the red mud was dried in a dryer, and its moisture content was 0.12wt% after drying. The dried red mud was ground and sieved, and the pass rate of the red mud dry powder with a fineness of 200 mesh was 92%. Then, the red mud was activated at 800°C using a high-temperature heating device, a muffle furnace, and the NaOH content of the activated dry powder activated red mud was 3.5wt%;

[0044] S2. The construction recycled micro powder and construction recycled sand were dried and sieved respectively. The passing rate of the construction recycled micro powder with a fineness of 0.075mm was 93%, and the CaO mass fraction detection value was 24.1%; the passing rates of the construction recycled sand with a particle size of 0.15mm-0.075mm and 0.3mm-0.15mm were 19% and 75% respectively, and the water content was 0.15wt%, the mud content was 1.3wt%, and the plasticity index was 5;

[0045] S3. 40 parts of dry activated red mud were mixed with 20 parts of building recycled powder, and dry mixed evenly in a mortar mixer for 90 seconds to make a solid waste cementitious material, and then the solid waste cementitious material was mixed with 30 parts of mortar recycled aggregate, and dry mixed evenly in a mortar mixer for 180 seconds to make a recycled mortar;

[0046] S4. Add 5 parts of recycled pigment and mix evenly. The color of the mortar is dark gray. Then add 1 part of high-fluidity water-reducing agent aminosulfonate and 1 part of anti-water seepage agent polyacrylamide and mix evenly. Automatically weigh through a packaging machine, and waterproof package and preserve for maintenance to obtain the colored self-leveling red mud-based fully recycled high-strength mortar.

[0047] In order to detect the performance of the colored self-leveling red mud-based fully recycled high-strength mortar material, cube and rectangular standard specimens were prepared, and their absolute dry compressive strength, absolute dry flexural strength and fluidity were tested. The results are shown in Table 1.

[0048] Table 1 Performance of colored self-leveling red mud-based fully recycled high-strength mortar in Example 1

[0049] Detection indicators Test results Absolute dry compressive strength / MPa 31.5 Absolute dry flexural strength / MPa 7.3 Initial fluidity / mm 186 30-minute fluidity / mm 181

[0050] Example 2

[0051] A colored self-leveling red mud-based fully recycled high-strength mortar comprises the following components in parts by mass: 70 parts of solid waste cementitious materials, including 45 parts of dry powder activated red mud and 25 parts of building recycled micro powder; mortar recycled aggregate: 35 parts of building recycled sand; 7 parts of recycled pigment; 4 parts of self-leveling agent: including 2 parts of high-fluidity water reducer and 2 parts of anti-seepage agent.

[0052] Among them, the pass rate of dry powder activated red mud with a fineness of 200 mesh is 96%, the NaOH content is 4.2wt%, and the water content is 0.18wt%; the CaO mass fraction of building recycled micropowder is 27.6%, and the pass rate of 0.075mm fineness is 91%; the pass rate of building recycled sand 0.15mm-0.075mm is 24%, the pass rate of 0.3mm-0.15mm is 83%, the water content is 0.31wt%, the mud content is 1.1wt%, and the plasticity index is 6; the recycled pigment is a waste pigment from a printer, the main colors are black, gray and red, and the particle size is 0.5 microns; in the self-leveling agent, the high-fluidity water reducer is aminosulfonate, and the anti-seepage agent is polyacrylamide.

[0053] The preparation process is as follows:

[0054] S1. First, the red mud was dried in a dryer, and its moisture content was 0.18% after drying. The dried red mud was ground and sieved, and the pass rate of the red mud dry powder with a fineness of 200 mesh was 96%. Then, the red mud was activated at 800°C using a high-temperature heating device, a muffle furnace, and the NaOH content of the activated dry powder activated red mud was 4.2wt%;

[0055] S2. The construction recycled micro powder and construction recycled sand were dried and sieved respectively. The passing rate of the construction recycled micro powder with a fineness of 0.075 mm was 91%, and the CaO mass fraction detection value was 27.6%; the passing rates of the construction recycled sand with a particle size of 0.15 mm-0.075 mm and 0.3 mm-0.15 mm were 24% and 83% respectively, and the water content was 0.31 wt%, the mud content was 1.1 wt%, and the plasticity index was 6;

[0056] S3. 45 parts of dry activated red mud were mixed with 25 parts of building recycled powder, and dry mixed evenly in a mortar mixer for 100s to make a solid waste cementitious material, and then the solid waste cementitious material was mixed with 35 parts of mortar recycled aggregate, and dry mixed evenly in a mortar mixer for 200s to make a recycled mortar;

[0057] S4. Add 7 parts of recycled pigment and mix evenly. The color of the mortar is dark brown. Then add 2 parts of aminosulfonate, a high-fluidity water-reducing agent, and 2 parts of polyacrylamide, an anti-seepage agent, and mix evenly. Automatically weigh through a packaging machine, and waterproof packaging and preservation for maintenance to obtain the colored self-leveling red mud-based fully recycled high-strength mortar.

[0058] In order to detect the performance of the colored self-leveling red mud-based fully recycled high-strength mortar, standard cube and rectangular specimens were prepared, and their compressive strength, flexural strength and fluidity were tested. The results are shown in Table 2.

[0059] Table 2 Performance of colored self-leveling red mud-based fully recycled high-strength mortar in Example 2

[0060] Detection indicators Test results Absolute dry compressive strength / MPa 34.6 Absolute dry flexural strength / MPa 7.5 Initial fluidity / mm 184 30-minute fluidity / mm 181

[0061] Example 3

[0062] A colored self-leveling red mud-based fully recycled high-strength mortar comprises the following components in parts by mass: 80 parts of solid waste cementitious materials, including 50 parts of dry powder activated red mud and 30 parts of building recycled micropowder; mortar recycled aggregate: 40 parts of building recycled sand; 8 parts of recycled pigment; 6 parts of self-leveling agent: including 3 parts of high-fluidity water reducing agent and 3 parts of anti-seepage agent.

[0063] Among them, the pass rate of dry powder activated red mud with a fineness of 200 mesh is 92%, the NaOH content is 3.9wt%, and the water content is 0.18wt%; the CaO mass fraction of building recycled micropowder is 32.7%, and the pass rate of 0.075mm fineness is 95%; the pass rate of building recycled sand 0.15mm-0.075mm is 31%, the pass rate of 0.3mm-0.15mm is 84%, the water content is 0.27wt%, the mud content is 1.7wt%, and the plasticity index is 5; the recycled pigment is a waste pigment from a printer, the main colors are black, yellow and red, and the particle size is 0.7 microns; in the self-leveling agent, the high-fluidity water reducer is aminosulfonate, and the anti-water seepage component is polyvinyl alcohol.

[0064] The preparation process is as follows:

[0065] S1. First, the red mud was dried in a dryer, and its moisture content was 0.18wt% after drying. The dried red mud was ground and sieved, and the pass rate of the red mud dry powder with a fineness of 200 mesh was 92%. Then, the red mud was activated at 800°C using a high-temperature heating device, a muffle furnace, and the NaOH content of the activated dry powder activated red mud was 3.9wt%;

[0066] S2. The construction recycled micro powder and construction recycled sand were dried and sieved respectively. The passing rate of the construction recycled micro powder with a fineness of 0.075 mm was 95%, and the CaO mass fraction detection value was 32.7%; the passing rates of the construction recycled sand with a particle size of 0.15 mm-0.075 mm and 0.3 mm-0.15 mm were 31% and 84% respectively, and the water content was 0.27 wt%, the mud content was 1.7 wt%, and the plasticity index was 5;

[0067] S3. 50 parts of dry activated red mud were mixed with 30 parts of building recycled powder, and dry mixed evenly in a mortar mixer for 110s to make a solid waste cementitious material, and then the solid waste cementitious material was mixed with 40 parts of mortar recycled aggregate, and dry mixed evenly in a mortar mixer for 220s to make a recycled mortar;

[0068] S4. Add 8 parts of recycled pigment and mix evenly. The color of the mortar is reddish brown. Then add 3 parts of aminosulfonate, a high-fluidity water-reducing agent, and 3 parts of polyvinyl alcohol, an anti-seepage agent, and mix evenly. Automatically weigh through a packaging machine, and waterproof package and preserve for maintenance to obtain the colored self-leveling red mud-based fully recycled high-strength mortar.

[0069] In order to detect the performance of the colored self-leveling red mud-based fully recycled high-strength mortar, standard cube and rectangular specimens were prepared, and their compressive strength, flexural strength and fluidity were tested. The results are shown in Table 3.

[0070] Table 3 Performance of colored self-leveling red mud-based fully recycled high-strength mortar in Example 3

[0071] Detection indicators Test results Absolute dry compressive strength / MPa 30.2 Absolute dry flexural strength / MPa 7.1 Initial fluidity / mm 183 30-minute fluidity / mm 180

[0072] Example 4

[0073] A colored self-leveling red mud-based fully recycled high-strength mortar comprises the following components in parts by mass: 100 parts of solid waste cementitious materials, including 60 parts of dry powder activated red mud and 40 parts of building recycled micropowder; mortar recycled aggregate: 50 parts of building recycled sand; 10 parts of recycled pigment; 10 parts of self-leveling agent: including 5 parts of high-fluidity water reducing agent and 5 parts of anti-seepage agent.

[0074] Among them, the pass rate of dry powder activated red mud with a fineness of 200 mesh is 97%, the NaOH content is 4.6wt%, and the water content is 0.11wt%; the CaO mass fraction of building recycled micropowder is 36.9%, and the pass rate of 0.075mm fineness is 96%; the pass rate of building recycled sand 0.15mm-0.075mm is 27%, the pass rate of 0.3mm-0.15mm is 80%, the water content is 0.42wt%, the mud content is 1.3wt%, and the plasticity index is 5; the recycled pigment is a waste pigment from a printer, the main colors are blue, purple and red, and the particle size is 0.5 microns; in the self-leveling agent, the high-fluidity water reducer is aminosulfonate, and the anti-seepage agent is polyvinyl alcohol.

[0075] The preparation process is as follows:

[0076] S1. First, the red mud was dried in a dryer, and its moisture content was 0.11wt% after drying. The dried red mud was ground and sieved, and the pass rate of the red mud dry powder was 97% at 200 mesh fineness. Then, the red mud was activated at 800°C using a high-temperature heating device muffle furnace. The content of the activated dry powder activated red mud was 4.6wt% after NaOH detection;

[0077] S2. The construction recycled micro powder and construction recycled sand were dried and sieved respectively. The passing rate of the construction recycled micro powder with a fineness of 0.075mm was 96%, and the CaO mass fraction detection value was 36.9%; the passing rates of the construction recycled sand with a particle size of 0.15mm-0.075mm and 0.3mm-0.15mm were 27% and 80% respectively, and the water content was 0.42wt%, the mud content was 1.3wt%, and the plasticity index was 5;

[0078] S3. 60 parts of dry activated red mud were mixed with 40 parts of building recycled powder, and dry mixed evenly in a mortar mixer for 120s to make a solid waste cementitious material, and then the solid waste cementitious material was mixed with 50 parts of mortar recycled aggregate, and dry mixed evenly in a mortar mixer for 240s to make a recycled mortar;

[0079] S4. Add 10 parts of recycled pigment and mix evenly. The color of the mortar is purple-red. Then add 5 parts of aminosulfonate, a high-fluidity water-reducing agent, and 5 parts of polyvinyl alcohol, an anti-seepage agent, and mix evenly. Automatically weigh through a packaging machine, and waterproof package and preserve for maintenance to obtain the colored self-leveling red mud-based fully recycled high-strength mortar.

[0080] In order to detect the performance of the colored self-leveling red mud-based fully recycled high-strength mortar, standard cube and rectangular specimens were prepared, and their compressive strength, flexural strength and fluidity were tested. The results are shown in Table 4.

[0081] Table 4 Performance of colored self-leveling red mud-based fully recycled high-strength mortar in Example 4

[0082] Detection indicators Test results Absolute dry compressive strength / MPa 36.6 Absolute dry flexural strength / MPa 7.9 Initial fluidity / mm 185 30-minute fluidity / mm 180

[0083] It can be found that the prepared colored self-leveling red mud-based fully recycled high-strength mortar has excellent properties, with an initial fluidity of 180±5mm, a 30-minute fluidity greater than 180mm, an absolute dry compressive strength of more than 30Mpa, and an absolute dry flexural strength of more than 7Mpa; in addition, the colored self-leveling red mud-based fully recycled high-strength mortar of the present invention is prepared from construction solid waste materials, red mud and waste pigments, which greatly reduces the pollution of solid waste materials to the environment, and has significant economic, social and environmental benefits.

[0084] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A colored self-leveling red mud-based fully recycled high-strength mortar, characterized in that: The composition includes the following components in parts by weight: Solid waste cementitious materials: 60-100 parts; Mortar recycled aggregate: 30-50 parts; Recycled pigment: 5-10 parts; Self-leveling agent: 2-10 parts.

2. The colored self-leveling red mud-based fully recycled high-strength mortar according to claim 1 is characterized in that: The solid waste cementitious material comprises dry powder activated red mud and building recycled micro powder.

3. The colored self-leveling red mud-based fully regenerated high-strength mortar according to claim 2 is characterized in that: The mass fractions of the dry powder activated red mud and building recycled micro powder are as follows: Dry powder activated red mud: 40-60 parts; Building recycled micro powder: 20-40 parts.

4. The colored self-leveling red mud-based fully recycled high-strength mortar according to claim 2 is characterized by: In the solid waste gelling material, the fineness of the dry powder activated red mud satisfies that the passing rate of 200 mesh is greater than 90%, the NaOH content is 3.5wt%-4.6wt%, and the water content is less than 0.3wt%.

5. The colored self-leveling red mud-based fully recycled high-strength mortar according to claim 2 is characterized by: The mass fraction of CaO in the building recycled micro-powder is greater than 20%, and the fineness of the building recycled micro-powder satisfies a pass rate of 0.075 mm of greater than 90%.

6. The colored self-leveling red mud-based fully recycled high-strength mortar material according to claim 1 is characterized by: The mortar recycled aggregate is construction recycled sand that has passed through two sieves of 0.15mm-0.075mm and 0.3mm-0.15mm. The particle size passing rate of construction recycled sand is as follows: 0.3mm-0.15mm: 75%-84%; 0.15mm-0.075mm: 19%-31%.

7. The colored self-leveling red mud-based fully recycled high-strength mortar according to claim 6 is characterized by: The construction regenerated sand meets the requirements of a water content of less than 0.5wt%, a mud content of no more than 2wt%, and a plasticity index of no more than 7.

8. The colored self-leveling red mud-based fully recycled high-strength mortar according to claim 1 is characterized by: The regenerated pigment is waste pigment of oil painting or waste pigment of printer, and the particle size does not exceed 1 micron. Common pigments are divided into black, gray, blue dark tones and red, yellow, green bright tones according to the brightness of the color.

9. The colored self-leveling red mud-based fully recycled high-strength mortar according to claim 1, characterized in that: The self-leveling agent comprises a high-fluidity water-reducing agent and an anti-seepage agent, wherein the high-fluidity water-reducing agent is aminosulfonate, and the anti-seepage agent is at least one of polyacrylamide and polyvinyl alcohol.

10. The method for preparing the colored self-leveling red mud-based fully regenerated high-strength mortar according to claims 1 to 9, characterized in that: The following steps are involved: S1. First, the red mud is dried in a dryer until its water content is less than 0.3wt%, and the dried red mud is ground and sieved to prepare a red mud dry powder with a fineness of more than 90% passing rate of 200 mesh, and then the red mud is activated at 800°C using a high-temperature heating device muffle furnace, and the NaOH content of the activated dry powder activated red mud must reach 3.5wt%-4.6wt%; S2. Dry and sieve the construction recycled micro powder and construction recycled sand respectively, requiring the construction recycled micro powder to have a fineness of 0.075 mm with a pass rate greater than 90%, and a CaO mass fraction detection value greater than 20%; The passing rates of the particle sizes of 0.15mm-0.075mm and 0.3mm-0.15mm for construction recycled sand are required to reach 19%-31% and 75%-84% respectively, and the testing indicators must meet the requirements of water content less than 0.5wt%, mud content not exceeding 2wt%, and plasticity index not exceeding 7; S3. The dry activated red mud is mixed with the building recycled powder, and the mixture is evenly dry mixed in a mortar mixer for 90-120s to form a solid waste cementitious material, and then the solid waste cementitious material is mixed with the recycled aggregate in the mortar, and evenly dry mixed in a mortar mixer for 180-240s to form a recycled mortar; S4. Add recycled pigment and mix evenly. The color of the mortar is the color of the design. Then add self-leveling agent and mix evenly. Automatically weigh through the packaging machine, and waterproof packaging and storage for maintenance; The colored self-leveling red mud-based fully recycled high-strength mortar has an initial fluidity of 180±5 mm, a 30-minute fluidity of greater than 180 mm, an absolute dry compressive strength of more than 30 MPa, and an absolute dry flexural strength of more than 7 MPa.

Citation Information

Cited By

  • High-homogeneity all-solid waste grouting material as well as preparation method and application thereof

    CN121426489A